PENGARUH PROFITABILITAS, LEVERAGE, RISK MANAGEMENT COMMITTEE, DEWAN KOMISARIS, UKURAN PERUSAHAAN TERHADAP ENTERPRISE RISK MANAGEMENT DISCLOSURE PADA PERUSAHAAN INFRASTRUKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2017-2021 - Brahmana, Taminta Karenina; Pasaribu, Dompak; Nainggolan, Arison (Jurnal Mahkota Bisnis (Makbis), 2023)
The aim of this research is to dissect the influence of company size, board of directors composition, committee composition, risk tolerance and leverage on ERM disclosure. There are a total of 96 infrastructure businesses included in this analysis, all of which were listed on the IDX between 2017 and 2021. The data used in this research is secondary data collected from financial reports and annual reports of infrastructure businesses available at www.idx. co.id. The sample size of 17 companies was determined using purposive sampling techniques, and the research followed these companies for a total of five years. Secondary data was collected through a combination of note-taking and a systematic review of existing literature. In this research, multiple linear regression analysis was used to analyze the data. Based on the results of this research, neither the profitability variable, leverage variable, risk management committee, board of commissioners, nor company size have a statistically significant influence on ERM disclosure. Company Risk Management Disclosures are not significantly influenced by testing all independent variables simultaneously. As much as 92.3 percent of the variation in the dependent variable can be attributed to factors not taken into account in this analysis, only 7.7 percent can be attributed to the independent variables.